Islamic finance and NCCs: Comparative insights from Malaysia, Indonesia, and El Salvador - Ema Izati Zull Kepili; Nik Hadiyan Nik Azman (Universiti Sains Islam Malaysia, 2025)
‘Abqari Journal. Volume 32, Issue 2 Page (185-201)